Risk assessment of type 2 diabetes mellitus among fisherman community in Beypore area of Kozhikode - Mutalik, Anirudh V.; Bhosale, Shankar Bapu; Pawar, Anant T. (International Journal Of Community Medicine And Public Health, 2017)
Background: In the past decade it has become obvious that the prevalence of type 2 diabetes is increasing very rapidly. Unless necessary and appropriate action is taken, it is predicted that there will be at least 350 million people in the world with type 2 diabetes by the year 2030. The aim of the study was to assess the risk for type 2 diabetes mellitus (T2DM) among fisherman community in Beypore area of Kozhikode.The objectives of the study were to identify the total number of participants with abnormal random blood sugar among Beypore fisherman community of Calicut; to identify risk factors associated with type 2 diabetes mellitus patients among Beypore fisherman community of Calicut. Methods: A cross sectional study was conducted among fisherman colony of Beypore area, Calicut. All the eligible participants according to inclusion and exclusion criteria were included in the study. An pretested and piloted Finnish Diabetes questionnaire modified according to local settings was used to map the screened participants. As the first step, history and basic anthropometry measurements was taken. Then each participant underwent physical examination. Further random blood glucose was calculated using strip glucometric method. Once confirmed, the treatment for type 2 diabetes was started. Results: Overall prevalence was found to be 29.23%. Prevalence of T2DM was significantly associated with age i.e. as age increases there is the risk of developing T2DM and p value was found to be significant. Conclusions: Age, educational status, central obesity and addiction are major risk factors for type 2 diabetes mellitus.